Methods of Analysis of the Nasal Profile: A Systematic Review with Meta-analysis. (16th March 2021) - Jankowska, Agnieszka; Janiszewska-Olszowska, Joanna; Jedliński, Maciej; Grocholewicz, Katarzyna
Abstract : The nose is the most prominent structure of the face, influencing facial appearance and profile. Orthodontists have an awareness of facial structures, including nasal morphology, when diagnosing and treatment planning. Maxillofacial surgeons influence facial profile by bimaxillary surgery, improving facial aesthetics and harmony. The aim of this review was to summarize the available methods of analysing nasal morphology and profile, and to assess their complexity. A literature search was conducted in PubMed, Scopus, Web of Science, and Embase using the following search terms: "nasal profile analysis", "nasolabial angle", and "nasal profile cephalometric" in order to select studies providing knowledge on correlations between occlusion and nasal development, differences between skeletal classes, ethnic variability, and differences between the sexes. Studies concerning genetic disorders were excluded. Finally, 17 full-text papers were analysed, which pertained to nasolabial angle, or facial profile including the nose. Data concerning methods, ethnic group, reference landmarks used, and measurements made were extracted and placed in tables. Numerous methods of nasal profile analysis can be found in the literature. These methods describe various numbers of parameters, which have influence on facial aesthetic. Nasal parameters are correlated to skeletal class and nasolabial angle, positions of upper incisors, and maxillary inclination.